Molecular Insights Into SARS COV-2 Interaction With Cardiovascular Disease: Role of RAAS and MAPK Signaling - Wehbe, Zena; Hammoud, Safaa; Soudani, Nadia; Zaraket, Hassan; El-Yazbi, Ahmed; Eid, Ali H. (Frontiers in Pharmacology, 2020)
In December 2019, reports of viral pneumonia came out of Wuhan city in Hubei province in China. In early 2020, the causative agent was identified as a novel coronavirus (CoV) sharing some sequence similarity with SARS-CoV that caused the severe acute respiratory syndrome outbreak in 2002. The new virus, named SARS-CoV-2, is highly contagious and spread rapidly across the globe causing a pandemic of what became known as coronavirus infectious disease 2019 (COVID-19). Early observations indicated that cardiovascular disease (CVD) patients are at higher risk of progression to severe respiratory manifestations of COVID-19 including acute respiratory distress syndrome. Moreover, further observations demonstrated that SARS-CoV-2 infection can induce de novo cardiac and vascular damage in previously healthy individuals. Here, we offer an overview of the proposed molecular pathways shared by the pathogenesis of CVD and SARS-CoV infections in order to provide a mechanistic framework for the observed interrelation. We examine the crosstalk between the renin-angiotensin-aldosterone system and mitogen activated kinase pathways that potentially links cardiovascular predisposition and/or outcome to SARS-CoV-2 infection. Finally, we summarize the possible effect of currently available drugs with known cardiovascular benefit on these pathways and speculate on their potential utility in mitigating cardiovascular risk and morbidity in COVID-19 patients.